2017
DOI: 10.1155/2017/5646247
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Cholestasis of Pregnancy Leading to Severe Vitamin K Deficiency and Coagulopathy

Abstract: Intrahepatic cholestasis of pregnancy is seldom associated with significant vitamin K deficiency. We report a case of a 16-year-old primigravid patient at 24 weeks and 3 days of gestation who presented with pruritus, hematuria, and preterm labor. Laboratory work-up showed severe coagulopathy with Prothrombin Time (PT) of 117.8 seconds, International Normalized Ratio (INR) of 10.34, and elevated transaminases suggestive of intrahepatic cholestasis of pregnancy. Her serum vitamin K level was undetectable (<0.1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 7 publications
(14 reference statements)
0
19
0
3
Order By: Relevance
“…However, it is ineffective in decreasing ALT levels and pruritus in ICP patients [42,43]. A common practice is the induction of labor at the 36th–38th week of gestation to lower the risk of intrauterine death [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is ineffective in decreasing ALT levels and pruritus in ICP patients [42,43]. A common practice is the induction of labor at the 36th–38th week of gestation to lower the risk of intrauterine death [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that ICP causes impaired absorption of fat-soluble vitamins (D, E, A, K) from the terminal ileum, due to altered enterohepatic circulation of bile acids. As the most important vitamin for coagulation, vitamin K is synthesized by the mother, and the fetus takes it by transplacental passage [14].…”
Section: Introductionmentioning
confidence: 99%
“…The high-level cholic acid, especially high CG, in pregnant women with ICP, may cause the shrinkage of the placental villus (16), thus, resulting in edema of the placental trophocytes. Despite the increased number, edema occurs in the basal villus, and the villous cavity remarkably declines (17), thus causing a significant reduction of maternal blood flow in the placental villus cavity, fetal hypoxia and intrauterine distress (18).…”
Section: Discussionmentioning
confidence: 99%
“…The biological significance of VK for the regulation of bile acids synthesis is not clear, but recently, Maldonado et al reported that VK deficiency is associated with intrahepatic cholestasis of pregnancy in certain patients. Low levels of VK may cause dysregulation of bile acid synthesis with concomitant upregulation of CYP7A1 and CYP8B1 expression levels, which occurs during the progression of this disease [ 38 ].…”
Section: Discussionmentioning
confidence: 99%